'Not the Wolf Itself': Distinguishing Hunters' Criticisms of Wolves from Procedures for Making Wolf Management Decisions. Issue 1 (2nd January 2020) - von Essen, Erica; Allen, Michael
ABSTRACT: Swedish hunters sometimes appeal to an inviolate 'right to exist' for wolves, apparently rejecting NIMBY. Nevertheless, the conditions existence hunters impose on wolves in practice fundamentally contradict their use of right to exist language. Hunters appeal to this language hoping to gain uptake in a conservation and management discourse demanding appropriately objective ecological language. However, their contradictory use of 'right to exist' opens them up to the charge that they are being deceptive – indeed, right to exist is a 'disguised NIMBY!' We address this situation by distinguishing hunters' criticisms of wolves from the procedures for reaching objective policy decisions.